The Implementation of Virtual Tourism: A Bibliometric and Visualization Analysis - Tran, Tuyen; Nguyen, Thi-Van Hanh; Warsiyah, Warsiyah (UUM Press, 2023)
Technology is a crucial part of the tourism industry; supporting businesses with daily operations, while improving customer experiences. Virtual reality (VR) has garnered considerable attention as an emerging technology with the potential to bring about substantial transformations in the tourism industry. Consequently, the concept of virtual tourism has emerged as a contemporary and contentious issue, generating diverse discussions. In the context of tourism digitalization and the growing trend of virtual tourism, a review for exploring the state of the art of this new kind of tourism is essential. This study employed systematic and narrative reviews to explore research domains and highlight an up-to-date insight into the current state of research on virtual tourism. Based on performance mapping and intellectual mapping, keywords and clusters analysis were implemented to explore the current state of research on virtual tourism and suggest some implications for future research agenda. The five clusters included (1) Visualization with computer graphics in cultural heritages; (2) Tourism issues, COVID-19, and virtual reality technology; (3) Virtual reality technology and application in tourism; (4) Virtual tourism characteristics and user experience; and (5) Cyber tourism, internet and information technology. Some implications for future research agenda had been introduced through the analysis of bibliographic coupling depicted by visualization of similarities (VOS) viewer application.